Fractionation of dibenzofurans during subsurface petroleum migration: Based on molecular dynamics simulation and reservoir geochemistry. (January 2018) - Li, Meijun; Liu, Xiaoqiang; Wang, T.-G.; Jiang, Weidong; Fang, Ronghui; Yang, Lu; Tang, Youjun
Highlights: The geochromatography of dibenzothiophenes was simulated by molecular dynamics. Two new indicators are proposed to trace oil charging pathways. Dibenzothiophenes were successfully applied in carbonate and sandstone reservoirs. The effects of maturity and depositional environment are discussed. Abstract: Dibenzofurans, oxygen-containing heterocyclic aromatics, are ubiquitous in crude oils. Their geochemical implications in petroleum geochemistry have been studied in numerous previous publications. Here, we present the distribution of dibenzofuran and its methylated homologues, and calculate the polarity and solubility of methyldibenzofuran isomers based on the Connolly surfaces and molecular dynamics simulation. The results show that the geo-chromatographic fractionation effect is evident due to absorption onto the water/silica matrix carrier bed during the oil migration process. Two potential molecular indicators relative to dibenzofurans, i.e. the total content of dibenzofurans and the relative abundances of 1-methyldibenzofuran to 4-methyldibenzofuran, are proposed for tracing the oil migration orientation and filling pathways. These two indicators were applied successfully in Paleozoic marine carbonate and Tertiary lacustrine sandstone reservoirs. The variations of source input, depositional environment, and maturity for oils from same source bed/kitchen appear to have no significant effect on these two indicators. It suggested that these two dibenzofuran indicators are potentially effective molecular tracers for orientation and filling pathways in oil migration.